One21: A Novel, Customizable Injection Protocol for Treatment of the Forehead with IncobotulinumtoxinA - de Sanctis Pecora C (Dove Medical Press, 2020)
Carla de Sanctis Pecora Dermatologie-Clínica, Cirurgia, Cosmiatria e Laser, São Paulo, BrazilCorrespondence: Carla de Sanctis Pecora Avenida Ibirapuera, 2907, Conj. 901, Moema, São Paulo, SP CEP: 04029-200, BrazilTel/Fax +55 11 50420871Email carla@dermatologie.com.brAbstract: It is well known that incobotulinumtoxinA (INCO) is an effective approved treatment for dynamic wrinkles of the upper face caused by the action of mimetic muscles over time. In doing so, it is important to maintain a balance between muscle groups and a natural facial appearance. Patients differ enormously in their facial anatomy regarding structure and function, both within and between genders, ethnicities, and age. Therefore, treating all patients with the same injection pattern and the same doses can result in undesired outcomes. There is a need for a tailored approach to achieve optimal results, as well as to increase patient satisfaction. With this in mind, the novel one21 injection technique which allows for individualized treatment has been developed for the treatment of horizontal forehead lines using INCO, resulting in a positive impact on eyebrow position and shape. This technique is the next step in a customized approach, giving natural-looking results and high patient satisfaction.Keywords: incobotulinumtoxinA, botulinum toxin, injection technique, one21, dynamic wrinkles, upper face